2013
DOI: 10.1080/00324728.2013.821153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional stress and socio-economic status on maternal mortality in six German villages, 1766–1863

Abstract: We examined the effects of nutritional stress on maternal mortality arising from short-term economic crises in eighteenth-century and nineteenth-century Germany, and how these effects might have been mitigated by socio-economic status. Historical data from six German villages were used to assess how socio-economic conditions and short-term economic crises following poor harvests may have affected maternal mortality. The results show that 1 year after an increase in grain prices the risk of maternal death incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…In addition, neonates from depleted mothers could also be more fragile and thus less able to counter adverse conditions such as cold weather. According to the maternal-depletion hypothesis (Winkvist, Rasmussen, and Habicht 1992), short inter-birth intervals generally impoverish the mother's physiological state, increasing neonatal mortality risks (DaVanzo et al 2008), as the mothers are not able to recover from the pregnancybreastfeeding cycle (DaVanzo et al 2008;Scalone 2014). Previous studies have suggested that the higher risks for very young mothers could be due to mother-fetus competition for nutrients or difficulties in maternal physical growth (Kramer and Lancaster 2010), whereas infants born to older mothers could be affected by a higher likelihood of maternal morbidity and congenital abnormality (Pozzi 2002;Carolan and Frankowska 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, neonates from depleted mothers could also be more fragile and thus less able to counter adverse conditions such as cold weather. According to the maternal-depletion hypothesis (Winkvist, Rasmussen, and Habicht 1992), short inter-birth intervals generally impoverish the mother's physiological state, increasing neonatal mortality risks (DaVanzo et al 2008), as the mothers are not able to recover from the pregnancybreastfeeding cycle (DaVanzo et al 2008;Scalone 2014). Previous studies have suggested that the higher risks for very young mothers could be due to mother-fetus competition for nutrients or difficulties in maternal physical growth (Kramer and Lancaster 2010), whereas infants born to older mothers could be affected by a higher likelihood of maternal morbidity and congenital abnormality (Pozzi 2002;Carolan and Frankowska 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In their review on global maternal mortality differentials, Ronsmans and Graham [ 10 ] pointed out that both large and small socioeconomic factors can affect maternal mortality. Similarly, in a study on several geographically separated villages in 18 th - and 19 th -century Germany, Scalone [ 11 ] found that local crop price fluctuations affected maternal mortality levels differently depending on the family’s social stratum.…”
Section: Introductionmentioning
confidence: 99%
“…8 While the central focus on safe motherhood strategies should remain, maternal nutrition may also be important in alleviating the risk of pregnancy-related mortality; its role, however, remains unrecognized and underappreciated. Even a recent analysis of historical data from 6 villages in Germany revealing increased risk of maternal death a year after a short-term nutrition crisis in the form of increased grain prices 9 indicates the nutritionÀmaternal health link. However, few studies have examined the association between poor nutritional status during pregnancy and risk of maternal death, largely due to lack of funding and adequate data to examine this relationship.…”
Section: Maternal Health and Birth Outcomesmentioning
confidence: 98%